What Does Androgen Receptor Signaling Pathway in Sertoli Cells During Normal Spermatogenesis Tell Us? - Wang, Jia-Ming; Li, Zhen-Fang; Yang, Wan-Xi (Frontiers in Endocrinology, 2022)
Androgen receptor signaling pathway is necessary to complete spermatogenesis in testes. It can be divided into classical-signaling pathway and non-classical signaling pathway depending on androgen binding location. As the only somatic cell type in seminiferous tubule, Sertoli cells are under androgen receptor signaling pathway regulation via androgen receptor in cytoplasm and plasma membrane. Androgen receptor signaling pathway is able to regulate biological processes in Sertoli cells as well as germ cells surrounded between Sertoli cells. Our review will summarize the major discoveries of androgen receptor signaling pathway in Sertoli cells and the paracrine action on germ cells from Sertoli cells. Androgen receptor signaling pathway regulates Sertoli cell proliferation and maturation, as well as maintain the integrity of blood-testis barrier between Sertoli cells. Also, Spermatogonia stem cells achieve a balance between self-renewal and differentiation under androgen receptor signaling regulation. Meiotic and post-meiotic processes including Sertoli cell-Spermatid attachment and Spermatid development are guaranteed by androgen receptor signaling until the final sperm release. This review also includes one disease related to androgen receptor signaling dysfunction named as androgen insensitivity syndrome. As a step further ahead, this review may be helpful for developing androgen therapies to cure infertility from Sertoli cells perspective.